2014
DOI: 10.1111/cas.12393
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic approach for cancer cells in urine sediments by 5‐aminolevulinic acid‐based photodynamic detection in bladder cancer

Abstract: Bladder urothelial carcinoma is diagnosed and followed up after transurethral resection using a combination of cystoscopy, urine cytology and urine biomarkers at regular intervals. However, cystoscopy can overlook flat lesions like carcinoma in situ, and the sensitivity of urinary tests is poor in low-grade tumors. There is an emergent need for an objective and easy urinary diagnostic test for the management of bladder cancer. In this study, three different modalities for 5-aminolevulinic acid (ALA)-based phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…In the present study, 5‐ALA‐induced fluorescent selective upper tract urinary cytology was more sensitive (90.4%) than conventional selective upper tract urinary cytology (60.3%), regardless of patient age, sex, pT stage and tumor grade. For BT, the same result was attained with 5‐ALA‐induced cytology using voided urine …”
Section: Discussionsupporting
confidence: 63%
“…In the present study, 5‐ALA‐induced fluorescent selective upper tract urinary cytology was more sensitive (90.4%) than conventional selective upper tract urinary cytology (60.3%), regardless of patient age, sex, pT stage and tumor grade. For BT, the same result was attained with 5‐ALA‐induced cytology using voided urine …”
Section: Discussionsupporting
confidence: 63%
“…5‐aminolevulinic acid (ALA) is widely used to induce protoporphyrin IX (PPIX), a photosensitizer used in photodynamic diagnosis and therapy for non‐muscle invasive bladder cancer . ALA is distributed ubiquitously in mammalian cells and is a precursor of tetrapyrole compounds such as heme, which is essential in aerobic energy metabolism and the electron transport system .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, similar experimental approaches were applied to a clinical trial, that is, directly exposing 5‐ALA to urinary cytology. The results showed that direct 5‐ALA exposure is efficient in discriminating between cancer and noncancer cells …”
Section: Discussionmentioning
confidence: 99%
“…Because of the relatively higher expression of the drug efflux transporter ABCG2 in cancer cells than in noncancer cells, Ko143 was found to alleviate cell‐to‐cell variability in PpIX‐FI. In practice, 5‐ALA combined with ABCG2 inhibitor treatment reduces cell‐to‐cell variability in PpIX‐fluorescence and enhances PpIX accumulation . In contrast, combined administration of 5‐ALA and Ko143 barely altered the PpIX‐FI in the noncancer cells MCF10A expressing low levels of the ABCG2 transporter.…”
Section: Discussionmentioning
confidence: 99%